Analysis Of Factors Affecting The Performance Paramedic At Hospital Royal Prima Medan - Suryani; Ermi Girsang; Sri Lestari Ramadhani; Sri Wahyuni Nasution (CV. Inara, 2022)
Paramedics as human resources run health services in hospitals. Paramedic performance is closely related to the quality of hospital services. The purpose of this study is to analyze the factors that affect the performance of paramedics at RSU Royal Prima Medan. This type of research is quantitative research with a cross-sectional design. The location of this research was conducted at RSU Royal Prima Medan. The research sample is all paramedics at RSU Royal Prima Medan as many as 112 people. The survey data were analyzed using the chi-square test and logistic regression. The results showed that there was an influence of motivation on the performance of paramedics (p= 0.000 <0.05), there was an effect of ability on the performance of paramedics (p = 0.000 <0.05), there was an effect of knowledge on the performance of paramedics (p = 0.000 < 0.05). ), there is an effect of the work environment on the performance of paramedics (p= 0.000 < 0.05), there is the effect of incentives on the performance of paramedics (p = 0.000 < 0.05), there is an effect of promotion on the performance of paramedics at the Royal Prima Hospital Medan in 2021 (p= 0.000 < 0.05). The variable that most dominantly influences the performance of paramedics at RSU Royal Prima Medan in 2021 is the motivation variable with a p-value of 0.016, OR = 4.182 (95% CI = 1.300-13,448). So the suggestions in this study are expected that hospitals can minimize these factors by redesigning work to reduce role ambiguity and paramedic boredom at work. there is the effect of incentives on the performance of paramedics (p = 0.000 < 0.05), there is an effect of promotion on the performance of paramedics at the Royal Prima Hospital Medan in 2021 ( p = 0.000 < 0.05.